A review of persuasive technology and design to healthy lifestyle - Ji, Kang; Che Me, Rosalam; Kamarudin, Khairul Manami (Universiti Teknologi MARA, 2023)
Maintaining a healthy lifestyle plays a vital role in personal health and social development. However, many individuals encounter challenges in adhering to healthy behaviours, often struggling to sustain a healthy way of life. A significant portion of the available products related to healthy lifestyles on the market are designed with the intent of persuasion. They utilise various strategies of persuasion to influence behaviours, ultimately aiming to bring about behaviour change. To provide designers and researchers with more effective design solutions in future product design, this study conducted a study on the application of persuasion technology and persuasion strategies in healthy life and the Fogg Behavioural Model (FBM) by using ATLASti and PRISMA software. The analytical approach of a systematic literature review (SLR) provides a systematic analysis and objective assessment of the persuasive principles and strategies used in the persuasive design of products. The study underscored the significance of persuasive technology and design healthy lifestyle interventions. In this regard, the study highlighted the benefits of persuasive design across four dimensions: orientation, friendliness, interaction, and ethics. These insights collectively show the effectiveness of persuasive design approaches within the framework of promoting healthier lifestyles.